“The Pertinence of Intelligent System in the field of Digital Image Forensics” (International Journal of Engineering and Computer Science, 2017)
: Images and videos have become the main information carriers in the digital era. The expressive potential of visual media and the ease in their acquisition, distribution and storage is such that they are more and more exploited to convey information, even sensible. As a consequence, today images and videos represent a common source of evidence, both in every-day life controversies and in trials. The simplest video in TV news is commonly accepted as a certification of the truthfulness of the reported news. In a similar way, videosurveillance recording scan constitute fundamental probationary material in a court of law. Together with undoubted benefits, the accessibility of digital visual media brings a major drawback. Lately, the reliability of digital visual information has been questioned, due to the ease in counterfeiting both its origin and content. Digital image forensics is a brand new research field which aims at validating the authenticity of images by recovering information about their history. Two main problems are addressed in this paper are: the identification of the imaging device that captured the image, and the detection of traces of forgeries. Digital images have the problem of being easy to edit and to tamper. As a result, digital forensics is now an important field in image processing